The iron mineralization of Spongia officinalis L. (Porifera, Dictyoceratida) and its relationships with the collagen skeleton - Vacelet, J.; Verdenal, B.; Périnet, G. (Biology of the Cell, 1988)
Lepidocrocite (y FeOOH) granules are frequently found in the spongin fibers of some horny sponges. The granules also contain calcite and a small amount of goethite (a FeOOH). In the genus Spongia, the amount of iron is highly variable according to the habitat and to the age of the fiber. Some indications about the skeletal growth and structure can be inferred from the distribution of the biominerals and the arrangement of the crystallites: i.e. (1) Mineralization is a slow process in comparison with fiber formation; (2) Secondary connective fibers may have a discontinuous growth; (3) The collagen microfibrils display a definite arrangement in the successive spongin layers; (4) Although spongin is a collagen highly resistant in vitro to enzymatic digestion, the sponge is able to perform remodeling of its skeleton through autodigestion of the fibers.